2017
DOI: 10.1016/j.cell.2017.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Unconventional Translation in Neurodegeneration

Abstract: Eukaryotic translation is tightly regulated to ensure that protein production occurs at the right time and place. Recent studies on abnormal repeat proteins, especially in age-dependent neurodegenerative diseases caused by nucleotide repeat expansion, have highlighted or identified two forms of unconventional translation initiation: usage of AUG-like sites (near cognates) or repeat-associated non-AUG (RAN) translation. We discuss how repeat proteins may differ due to not just unconventional initiation, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 58 publications
0
44
0
1
Order By: Relevance
“…Ribosome profiling demonstrated that initiation to near‐cognate codons is more common than previously thought and may occur in up to ~30% of mammalian genes (Ingolia et al , ; Fritsch et al , ). These data suggest that translation initiation at near‐cognate codons located upstream of the repeats could be a common pathogenic mechanism in microsatellite expansion diseases, a hypothesis that may warrant further investigations (Gao et al , ). However, translation initiation at near‐cognate codons should occur independently of the presence of downstream repeats, but DPR proteins are observed only in carriers of G4C2 repeat expansions and not in control individuals.…”
Section: Discussionmentioning
confidence: 82%
“…Ribosome profiling demonstrated that initiation to near‐cognate codons is more common than previously thought and may occur in up to ~30% of mammalian genes (Ingolia et al , ; Fritsch et al , ). These data suggest that translation initiation at near‐cognate codons located upstream of the repeats could be a common pathogenic mechanism in microsatellite expansion diseases, a hypothesis that may warrant further investigations (Gao et al , ). However, translation initiation at near‐cognate codons should occur independently of the presence of downstream repeats, but DPR proteins are observed only in carriers of G4C2 repeat expansions and not in control individuals.…”
Section: Discussionmentioning
confidence: 82%
“…Since the initial discovery of RAN translation, additional microsatellite expansion disorders including Fragile X Tremors Ataxia Syndrome (FXTAS) and Huntingtin’s disease have been added to the list of conditions in which bidirectional expanded transcripts produce RAN proteins [4, 5]. These novel and unexpected peptides contribute to toxicity challenging existing paradigms about disease mechanisms wherever they are found.…”
Section: Ran Translation Beyond Als/ftdmentioning
confidence: 99%
“…A version of IRES translation is Repeat Associated Non-AUG (RAN) translation (Fig. 11.1bii), which has been associated with mutant microsatellite expansions in traditionally noncoding portions of the genome such as untranslated regions (UTRs) or introns, and more recently with coding regions (recently reviewed in [4, 5]). In the absence of an AUG codon, translation is possible because the hairpin structure formed by microsatellite mRNA can mimic the methionine tRNA that initiates translation [6].…”
Section: Introductionmentioning
confidence: 99%
“…At other repeats and cellular contexts, RAN translation may utilize cap-independent initiation mechanisms and/ or initiator tRNAs other than tRNAi Met [10,39,40]. Which mechanisms occur in the context of each human disease is unclear and could vary based on gene context, repeat content, and cell type [19,41,42].…”
Section: Introductionmentioning
confidence: 99%